2019
DOI: 10.3389/fped.2019.00061
|View full text |Cite
|
Sign up to set email alerts
|

Severe Facial Herpes Vegetans and Viremia in NFKB2-Deficient Common Variable Immunodeficiency

Abstract: With the accessibility of next-generation sequencing modalities, an increasing number of primary immunodeficiency disorders (PIDDs) such as common variable immunodeficiency (CVID) have gained improved understanding of molecular pathogenesis and disease phenotype with the identification of a genetic etiology. We report a patient with early-onset CVID due to an autosomal dominant loss-of-function mutation in NFKB2 who developed a severe herpes vegetans cutaneous infection as well as concurrent herpes simplex vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…This complication has also been documented in various IEIs. 270,276 In immunodeficient patients with rapidly growing cutaneous masses, herpes simplex vegetans should be included in the differential diagnoses.…”
Section: Herpes Vegetansmentioning
confidence: 99%
See 2 more Smart Citations
“…This complication has also been documented in various IEIs. 270,276 In immunodeficient patients with rapidly growing cutaneous masses, herpes simplex vegetans should be included in the differential diagnoses.…”
Section: Herpes Vegetansmentioning
confidence: 99%
“…Acyclovir or related agents have been useful in patients with IEI 277 . Foscarnet was used successfully in a patient with NFKB2 deficiency 270 . Subcutaneous pegylated interferon‐α 2b has been used in recalcitrant cases, starting at a dose of 0.6 μg/kg/week, followed by 1 μg/kg/week 277 …”
Section: Augmented Induction Of Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond antibodies to IFNa, IFNv and IL-12 in patients with partial RAG deficiency [14,36] and APECED [37], Rosenberg et al [38] reported neutralizing anti-IFNa antibodies among patients with IPEX in two large cohorts from Seattle Children's Hospital and San Rafaelle Hospital (Milan, Italy). Anti-IFNv antibodies were recently described in a patient with NFkB2 deficiency after herpes virus infection [39]. In addition, novel autoantibodies against lung-specific bactericidal/permeabilityincreasing fold-containing protein B1 (BPIFB1) and the potassium channel regulator protein (KCNFG), have been linked to onset of autoimmune pneumonitis in disorders of central T-cell tolerance (APECED, RAG deficiency, and thymoma) [39].…”
Section: Patients With Pid Tend To Have Broad Selection Of Autoantibodies As Seen In Rag Deficiency With Aics [20 Andmentioning
confidence: 99%
“…Anti-IFNv antibodies were recently described in a patient with NFkB2 deficiency after herpes virus infection [39]. In addition, novel autoantibodies against lung-specific bactericidal/permeabilityincreasing fold-containing protein B1 (BPIFB1) and the potassium channel regulator protein (KCNFG), have been linked to onset of autoimmune pneumonitis in disorders of central T-cell tolerance (APECED, RAG deficiency, and thymoma) [39]. It is intriguing that presence of anticytokine antibodies are also proposed as markers of prognosis in APECED, as they noted negative correlation of anti-IFNa antibodies and the incidence of T1DM [40,41].…”
Section: Patients With Pid Tend To Have Broad Selection Of Autoantibodies As Seen In Rag Deficiency With Aics [20 Andmentioning
confidence: 99%